Criterios para la toma de decisiones en publicidad entre gerentes de marketing: un análisis cualitativo - Garay Acuña, Dante Daniel Alonso (2020)
Several studies mention that experience, feeling and knowledge are the factors that intervene in a purchase decision influenced by advertising stimuli. However, there is little literature exploring the criteria of marketing managers on how they understand how advertising works on individuals. The way of understanding this phenomenon determines their decisions and assessment of advertising effectiveness. This exploratory study aims to identify the criteria behind marketing managers in their advertising decisions and whether they are grounded on a theoretical model or an empirical framework. A qualitative methodology was used, based on interviews to marketing managers from the city of Lima. The qualitative analysis was done using a descriptive coding technique. The results indicate that their decisions are grounded on life experiences, on which they generate their own theoretical models to establish the advertising investment.